Peningkatan Literasi Pada Siswa-Siswi SMA Vita Surabaya Melalui Media Daring - Dewa Gde Satrya; Thomas Stefanus Kaihatu; Lexi Pranata (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
Often a business that has been based on a Business Contract creates a dispute by the parties. Business law disputes do not only include civil disputes but can turn to criminal law. This is also what has been complained about and experienced by several entrepreneurs who are members of the Malang Raya Entrepreneurs House (RPMR). Therefore, it is very important for people who are involved in the business world to understand the concept of contract law and dispute resolution of business contract law. The methods used by the Service Team are: 1) identifying problems with RPMR members related to business disputes, 2) Legal counseling conducted face-to-face and through radio broadcasts; 3) Legal Assistance by opening a legal consultation post and direct visits to several members of MSMEs; and 4) evaluation of Service Activities. The implementation of this service activity shows that there is an increase in the knowledge and skills of the participants in analyzing business contract disputes, resolving disputes that are being faced, and dealing with and/or preventing actions/things that have the potential to cause business disputes.